A face at the window - Graves, Sarah, 1951- (Graves, Sarah, 1951- Home repair is homicide mystery., 2009)
After more than three decades eluding justice, the man who murdered Jacobia "Jake" Tiptree's mother is finally about to stand trial--until he vanishes into thin air. Jake has a terrible foreboding of where Ozzie Campbell will turn up next. And while the local police chief is sure she's overreacting, the truth is far worse than even Jake's worst fears.